The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1080/00918369.2011.605740
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Analysis of Faculty Advocacy on LGBT Issues on Campus

Abstract: Faculty activism is an integral part of shared governance in higher education institutions, yet little is known about the dynamics that underlie this activism. Using oral history interviews with 30 faculty members working to secure lesbian, gay, bisexual, and transgender (LGBT)-supportive policies on their respective campuses, this article identifies reasons the faculty members became involved in this advocacy, types of advocacy in which they engaged, factors associated with engaging in advocacy, and challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…In order to effectively expand cohort-specific knowledge and clarify perceptions of LGBT legal, psychosocial, well aging, and health care issues, educators and practitioners alike must ensure expansion and infusion of such topics within the classroom (Logie et al, 2007;Gezinski, 2009;Craig et al, 2014), agency settings, field placements (Messinger, 2011) and counseling offices alike while measuring competency whenever possible. This may be accomplished though broader and ongoing discussions related to policy, advocacy, social justice, and civil rights in order to effectively advocate and increase knowledge of LGBT aging (McFarland & Sanders, 2003), lifespan, and psychosocial issues.…”
Section: Discussionmentioning
confidence: 99%
“…In order to effectively expand cohort-specific knowledge and clarify perceptions of LGBT legal, psychosocial, well aging, and health care issues, educators and practitioners alike must ensure expansion and infusion of such topics within the classroom (Logie et al, 2007;Gezinski, 2009;Craig et al, 2014), agency settings, field placements (Messinger, 2011) and counseling offices alike while measuring competency whenever possible. This may be accomplished though broader and ongoing discussions related to policy, advocacy, social justice, and civil rights in order to effectively advocate and increase knowledge of LGBT aging (McFarland & Sanders, 2003), lifespan, and psychosocial issues.…”
Section: Discussionmentioning
confidence: 99%
“…Making campuses welcoming and inclusive spaces for LGBT students is a priority for many universities nationwide (Messinger, 2009(Messinger, , 2011. Accordingly, many institutions implement LGBT speakers bureaus, ally/safe space programs, and other educational programs that aim to promote awareness, understanding, and acceptance of LGBT people (Draughn, Elkins, & Roy, 2002;Poynter & Tubbs, 2008;Rankin, 2005).…”
mentioning
confidence: 99%
“…Support and advocacy within each of these unique environments are key to positively influencing identity formation and the decision to disclose, as well as impact the fulfillment of broader developmental and educational tasks (Messinger, 2011). Key factors for increasing LGBTQ inclusiveness on campuses identified by Rankin (2005) include increased sensitivity in various facets of student life and providing institutional support through social outlets, housing, and supportive policies which can ultimately affect LGBTQ social work student outness.…”
Section: Institutional Factorsmentioning
confidence: 99%
“…Openly out faculty, staff, and administrators can positively influence LGBTQ social work students (Cain, 1996;D'Emilio, 1987;Donadello, 1986;Messinger, 2011). Hylton (2005) found that faculty disclosure of sexual identity often benefits their LGBTQ students, as 'out' faculty become invaluable resources and supportive role models.…”
Section: Faculty Outnessmentioning
confidence: 99%
See 1 more Smart Citation